2022
DOI: 10.3389/fvets.2022.939377
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine Regulates Immune Function and Gut Microbiota in DSS-Induced Ulcerative Colitis

Abstract: Nuciferine, a major aporphine alkaloid obtained from the leaves of Nelumbo nucifera, exhibits anti-cancer and anti-inflammatory properties; however, its protective effects against inflammatory bowel diseases (IBD) has never been explored. In this study, an ulcerative colitis (UC) model was established in BALb/c mice by the continuous administration of 5% dextran sulfate sodium (DSS) in drinking water for 1 week. From day 8 to day 14, the DSS-treated mice were divided into a high-dose and a low-dose nuciferine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Meanwhile, upregulation of anti-inflammatory cytokine IL-10 and IL-4 might inhibit the induced inflammation. Our previous studies had found that Nuciferine , a major bioactive component of lotus leaves, could improve intestinal inflammation induced by DSS ( Zhu et al, 2022 ). Thus, it was concluded that LLE-injected could inhibit the expression of inflammation-related genes through the TLR4/NF-κB signaling pathway, thereby alleviating oviduct inflammation in mixed bacteria-challenged laying hens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, upregulation of anti-inflammatory cytokine IL-10 and IL-4 might inhibit the induced inflammation. Our previous studies had found that Nuciferine , a major bioactive component of lotus leaves, could improve intestinal inflammation induced by DSS ( Zhu et al, 2022 ). Thus, it was concluded that LLE-injected could inhibit the expression of inflammation-related genes through the TLR4/NF-κB signaling pathway, thereby alleviating oviduct inflammation in mixed bacteria-challenged laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Like other traditional Chinese medicine, lotus leaves are also characterized by multiple components, targets, and pathways for treating diseases. Although there is evidence that lotus leaves may provide an anti-inflammatory and immunoenhancement effect on the chicken, the effect and specific mechanism (active components, specific targets, and pathways) on salpingitis of laying hens is still unclear ( Cheng et al, 2021 ; Zhu et al, 2022 ). With the development of technology, different hyphenated chromatography techniques are more and more applied to the analysis of components, especially liquid chromatography-mass spectrometry (UPLC-Q-TOF-MS) ( Abdullah AlFaris et al, 2020 ; Feng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Except for improving metabolic activity, nuciferine can also regulate the immune response and alleviate inflammation. For example, intraperitoneal injection of nuciferine could promote the growth of Lachnospiraceae, _Clostridium , Bilophila and Halomonas , whereas inhibit the proliferation of Bacteroides , Parabacteroides , and Paraprevotella , further improve the Th1/Th2 and Treg/Th17 balance, and attenuate inflammatory cell infiltration in ulcerative colitis mice ( Zhu et al, 2022 ). Similarly, supplementation with Nelumbinis Folium extract enhanced thymus index, spleen index, and bursa index, along with increased serum interleukin 2 (IL-2), total immunoglobulin G (IgG) and secretory immunoglobulin A (sIgA) concentrations, which correlated with the remodeling of gut microbiota ( Cheng et al, 2021 ).…”
Section: Gut Microbiota Is a Bridge Linking Pharmacological Effect Of...mentioning
confidence: 99%
“…Numerous studies have also demonstrated the ability of NPs to improve IBD symptoms by modulating immune metabolic processes in experimental IBD models. For example, nuciferine, an alkaloid, can improve DSS-induced UC in mice by regulating the differentiation of T cells and IgA+ B220+ B cells and restoring the balance of Th17/Treg and CD4+/CD8+ [ 215 ]. Similarly, celastrol improves Treg/Th1 and Treg/Th17 homeostasis in UC mice to maintain immune homeostasis in the gut [ 155 ].…”
Section: Major Pathways Of Action Of Nps In the Treatment Of Ibdmentioning
confidence: 99%